Association between anti-thymocyte globulin exposure and survival outcomes in adult unrelated haemopoietic cell transplantation: a retrospective, pharmacodynamic cohort analysis. Issue 4 (April 2017) - Admiraal, Rick; Nierkens, Stefan; de Witte, Moniek A; Petersen, Eefke J; Fleurke, Ger-jan; Verrest, Luka; Belitser, Svetlana V; Bredius, Robbert G M; Raymakers, Reinier A P; Knibbe, Catherijne A J; Minnema, Monique C; van Kesteren, Charlotte; et al.
Summary: Background: Anti-thymocyte globulin (ATG) is used to prevent graft-versus-host disease (GvHD) after allogeneic haemopoietic cell transplantation (HCT). However, ATG can also cause delayed immune reconstitution of T cells, negatively affecting survival. We studied the relation between exposure to ATG and clinical outcomes in adult patients with acute leukaemia and myelodysplastic syndrome. Methods: We did a retrospective, pharmacokinetic-pharmacodynamic analysis of data from patients with acute lymphoid leukaemia, acute myeloid leukaemia, or myelodysplastic syndrome receiving their first T-cell repleted allogeneic peripheral blood stem cell HCT with ATG (thymoglobulin) as part of non-myeloablative conditioning from March 1, 2004, to June 1, 2015. Patients received a cumulative intravenous dose of 8 mg/kg divided over 4 days, starting on day −8 before HCT. Active ATG concentrations were measured using a validated bioassay and pharmacokinetic exposure measures (maximum concentration, concentration at time of infusion of the graft, time to reach a concentration of 1 arbitary unit [AU] per day/mL, area under the curve [AUC], and the AUC before and after HCT) were calculated with a validated population pharmacokinetic model. The main outcome of interest was 5-year overall survival, defined as days to death from any cause or last follow-up. Other outcomes were relapse-related mortality, non-relapse mortality, event-free survival, acute and chronic GvHD, and assessment of current and optimum dosing. We used Cox proportional hazard models and Fine-Gray competing risk models for the analyses. Findings: 146 patients were included. ATG exposure after HCT was shown to be the best predictor for 5-year overall survival. Optimum exposure after transplantation was determined to be 60–95 AU per day/mL. Estimated 5-year overall survival in the group who had optimum exposure (69%, 95% CI 55–86) was significantly higher than in the group who had below optimum exposure (32%, 20–51, p=0·00037; hazard ratio [HR] 2·41, 95% CI 1·15–5·06, p=0·020) and above optimum exposure (48%, 37–62, p=0·030; HR 2·11, 95% CI 1·04–4·27, p=0·038). Patients in the optimum exposure group had a greater chance of event-free survival than those in the below optimum exposure group (HR 2·54, 95% CI 1·29–5·00, p=0·007; HR for the above optimum group: 1·83, 0·97–3·47, p=0·063). Above-optimum exposure led to higher relapse-related mortality compared with optimum exposure (HR 2·66, 95% CI 1·12–6·31; p=0·027). Below optimum exposure increased non-relapse mortality compared with optimum exposure (HR 4·36, 95% CI 1·60–11·88; p=0·0040), grade 3–4 acute GvHD (3·09, 1·12–8·53; p=0·029), but not chronic GvHD (2·38, 0·93–6·08; p=0·070). Modelled dosing based on absolute lymphocyte counts led to higher optimum target attainment than did weight-based dosing. Interpretation: Exposure to ATG affects survival after HCT in adults, stressing the importance of optimum ATG dosing. Individualised dosing of ATG, based on lymphocyte counts rather than bodyweight, might improve survival chances after HCT. Funding: Netherlands Organization for Health Research and Development and Queen Wilhelma Fund for Cancer Research.